How sport governance impacted on Olympic legacy: a study of unintended consequences and the 'Sport Makers' volunteering programme†. Issue 2 (3rd March 2016) - Nichols, Geoff; Grix, Jonathan; Ferguson, Gemma; Griffiths, Mark
Abstract : This paper focuses on Sport England's Sport Makers programme – which aimed to generate new sports volunteers as part of a 2012 Olympic and Paralympic Games legacy – as an illustration of the unintended consequences of a 'top-down', managerialist governance system. Interviews with county sport partnerships (CSPs), programme partners and workshop facilitators show that performance indicators imposed by Sport England distorted the programme: CSPs were obliged to meet targets – the process forcing a focus on 'soft' targets and incentivising double counting with existing programmes – instead of using their autonomy to promote volunteering most effectively. The paper contributes to the critique of new managerialism of public services by showing how this style of management proved counterproductive to achieving the programme aims, and failed to deliver sport policy nearer to the end-user and with relative autonomy from the state, which appears, paradoxically, to be more in command than in the era of 'top-down' government.